Implementation of Safety Management System in Improving Ship Crew Work Safety - Ofel Yericho Todingan; K.P. Suharyono S. Hadiningrat; Verry Albert Jekson Mardame Silalahi (JIPOWER : Journal of Intellectual Power, 2025)
The importance of occupational safety in the maritime industry encourages the implementation of the Safety Management System (SMS) to reduce the risk of accidents and improve protection for ship crews. This study aims to analyze the role of SMS in improving work safety, identifying implementation challenges, and its impact on incident reduction. The research method uses a qualitative approach with literature analysis and case studies to explore the complexity of SMS implementation in the maritime sector. The results show that effective SMS consists of four main components: safety policy, risk management, safety assurance, and safety promotion. Its implementation involves risk assessment, ongoing training, and periodic evaluation. However, challenges such as a lack of management commitment, an unsupportive organizational culture, and limited resources often hinder the success of SMS. Nonetheless, companies that successfully implement SMS experience increased safety awareness, reduced incidents, and the formation of a strong safety culture among crews. In conclusion, SMS is a crucial tool to improve work safety in the maritime sector. Its success depends on management commitment, crew training, and technology integration. Research recommendations include longitudinal studies to assess the long-term impact of SMS as well as quantitative approaches to objectively measure its effectiveness. These findings make a practical contribution for shipping companies and regulators in optimizing safety policies.